2022
DOI: 10.3390/foods11182825
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Empirical Mathematical Modeling, Energy and Exergy Analysis, and Textural Characteristics of Convectively Dried Plantain Banana Slices

Abstract: Thin-layer convective drying of plantain banana was performed at four different temperatures from 50 to 80 °C, with slice thicknesses from 2 to 8 mm. The drying curves, fitted to seven different semi-empirical mathematical models, were successfully used to fit experimental data (R2 0.72–0.99). The diffusion approach had better applicability in envisaging the moisture ratio at any time during the drying process, with the maximum correlation value (R2 0.99) and minimum value of x2 (2.5×10−5 to 1.5×10−4) and RMSE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
(60 reference statements)
0
2
0
Order By: Relevance
“…). Several researchers, such asZhang et al (2020),Kamble et al (2022),Kaveh et al (2023b), andLin et al (2023), have found similar results regarding the impact of drying temperature and thickness on the SEC of the drying process of different products. The value of specific energy consumption has been reported by other researchers for berberis fruit from 20.93 to 1110.07 kWh/kg(Aghbashlo et al, 2008), orange from 186.87 to 337.81 kWh/kg(Çetin, 2022), pumpkin from 88.78 to 669.70 kWh/kg(Taşova & Öcalan, 2023), bitter melon from 160 to 309 kWh/kg (AkhoundzadehYamchi et al, 2024), corn from 129.95 to 227.63 kWh/kg(Ononogbo et al, 2021), and onion from 41.28 to 82.94 kWh (…”
mentioning
confidence: 63%
“…). Several researchers, such asZhang et al (2020),Kamble et al (2022),Kaveh et al (2023b), andLin et al (2023), have found similar results regarding the impact of drying temperature and thickness on the SEC of the drying process of different products. The value of specific energy consumption has been reported by other researchers for berberis fruit from 20.93 to 1110.07 kWh/kg(Aghbashlo et al, 2008), orange from 186.87 to 337.81 kWh/kg(Çetin, 2022), pumpkin from 88.78 to 669.70 kWh/kg(Taşova & Öcalan, 2023), bitter melon from 160 to 309 kWh/kg (AkhoundzadehYamchi et al, 2024), corn from 129.95 to 227.63 kWh/kg(Ononogbo et al, 2021), and onion from 41.28 to 82.94 kWh (…”
mentioning
confidence: 63%
“…2, drying methods and carrier agent rates affected the effective diffusion values of the drying processes. It has been observed that the effective diffusion values of convective drying methods are higher than microwave drying methods [21]. The reason for this is that microwave drying methods carry out the drying process by creating a pressure difference in the product, causing the moisture moving away from the product to move forward.…”
Section: Effective Moisture Diffusionmentioning
confidence: 99%